Sintesis, Karakterisasi dan Aplikasi Karbon Aktif dari Kulit Pisang - Muhammad Patly; Edi Nasra; Sri Benti Etika; Umar Kalmar Nizar (Jurnal Periodic Jurusan Kimia UNP, 2020)
Active Carbon from biomassa has been ideal material as absorbent of pollutant chemistry. Banana peel is a biomassa contain about 60% carbohydtrate and its existence is abundant in nature, it causes banana peel is great for making active carbon. This review is combination from some researches about active carbon from banana peel. It aims to comprehend the carbon active synthesis from banana peel, characterization of active carbon and application active carbon as absorbent chemical pollution. The result from this review show characteristic of active carbon as functional groups,crystalline structure, surface morphology, pore size and pore volume, percentage of absoption and absorption capacity of active carbon to pollutant chemistry.